Exploring Generation Z's Perceptions and Expectations of Organizational Culture and Leadership Style in the Indonesian Automotive Manufacturing Industry: A Phenomenological Study - Mitia Intansari; Okder Pendrian (Green Publisher Indonesia, 2026)
Generation Z now constitutes over 23% of Indonesia's workforce, yet the automotive manufacturing industry characterized by hierarchical culture, zero-error tolerance, and outcome orientation faces persistent challenges of quiet quitting and high turnover among young employees. This research explores Generation Z (Gen Z) employees' perceptions and expectations regarding organizational culture and leadership styles within Indonesia's automotive manufacturing industry. Driven by phenomena of quiet quitting and high turnover rates among young workers, this research employed a qualitative phenomenological approach. In-depth semi-structured interviews were conducted with eight informants four Gen Z employees and four direct supervisors at PT XYZ, a major two-wheeled vehicle manufacturer. Results reveal that Gen Z perceives the industry as a zero-error tolerance environment and does not categorically reject authoritative leadership when functional-technical in nature. However, they strongly expect a shift toward a learning culture and coaching/mentoring leadership. Loyalty is not directed toward the organization abstractly but toward direct supervisors who act as 'cultural filters.' Motivation is driven by structured technical challenges and expert power recognition. The research recommends 'extreme accountability' strategies granting greater ownership to young employees to enhance engagement and retention in the Industry 4.0 era.